Pengaruh Ekstrak Mengkudu (Morinda citrifolia) Terhadap Penurunan Tekanan Darah Pada Tikus Putih Wistar Jantan Dengan Hipertensi - Pipit Festi W (THE JOURNAL OF MUHAMMADIYAH MEDICAL LABORATORY TECHNOLOGIST, 2020)
Hypertension is one of the most important causes of early death because it is closely related to the risk of cardiovascular disease. The prevalence of hypertension continues to increase with lifestyle changes. Non-pharmacological management is an alternative in the treatment of hypertension, one of which is complementary therapy by consuming herbal ingredients. The purpose of this study was to determine the effect of noni extract on reducing blood pressure in male  Wistar experimental-rats.The research design used was pre experimental design. One group pre-test post test design with purposive sampling technique. Number of samples were 16 male Wistar experimental-rats . The instrument in this study was the observation sheet and blood pressure measurement for taicap blod pressure. Statistical test analysis using Wilcoxon test.The results showed blood pressure before being given noni extract, cystolic pressure 150.93 mmHg, diastole pressure 112.87 mmHg. After administration of noni extract average blood pressure systole: 110,625 mmHg, diastole blood pressure average 85,125 mmHg Wilcoxon statistical test results showed that p = 0,000 <a = 0.05 showed a decrease in blood pressure before and after giving of noni extractThe conclusion from the study showed that there was an effect of noni extract on reducing blood pressure in hypertensive male Wistar experimental-mouse. Development of natural ingredients in the management of non-pharmacological hypertension needs to be done at the dose and effectiveness.                      Keywords: Hypertension, Noni extract, white rat.